PANDANGAN ISLAM TERHADAP SOSOK WANITA - Syamsiah Nur (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2021)
Women are very noble creatures created by Allah SWT. Islam elevates a woman's status so that she becomes one of the important aspects in worshiping Allah SWT. Basically, women have special rights in which they should be honored. Islam views women as a gift from Allah SWT. With him, men will get inner and outer peace, and are able to provide very useful positive energy, such as a sense of love, affection, and life motivation. In Islam, women and men are the same. Both creatures of Allah SWT, both worship Allah SWT, and their reward is according to their tests and deeds.